PERAN BIMBINGAN DAN KONSELING DALAM MENGURANGI KECANDUAN MEDIA SOSIAL PADA PESERTA DIDIK - Adinda Novia Wahyuningrum (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
The purpose of this study is to analyze the role of guidance and counseling in reducing social media addiction in students. The method used in this research is Systematic Literature Review (SLR), which is to find data or literature from journals and articles to be identified, evaluated, processed and analyzed. This research indicates that guidance and counseling has 6 roles in reducing social media addiction in students, namely as a program planner, administrator, adviser, consultant, informer and tester. Based on the results of the study it can be concluded that guidance and counseling have many important roles in reducing social media addiction in students.